OC-150 A decade of change in the management of severe gastrointestinal haemorrhage. (28th May 2012) - Dhadwal, A S; Platt, E; Morad, E; Osborne, A; Watkinson, A; Wajed, S
Abstract : Introduction: Acute major gastrointestinal bleeding represents a serious and complex clinical challenge requiring a multi-modality approach involving endoscopic, radiological and surgical intervention. The optimal management of this condition has evolved significantly in recent years, and this retrospective study evaluated the changing trends in practice over a 10-year period. Methods: A comprehensive and retrospective analysis of all the patients treated for acute serious gastrointestinal haemorrhage (SGIH), not controllable by endoscopic therapy alone between 2001 and 2011 was performed. This time period overlaps the introduction of a dedicated 24-h interventional radiology service (2009). Baseline demographics, including Rockall and Glasgow Scores, and outcomes from interventional radiological and/or surgical intervention were analysed. Results: Ninety-nine patients in the 10-year period required radiological or surgical intervention for SGIH with a median age of 70 years old (range 22–93). Sixty-seven patients (68%) were treated with surgery alone, with a successful outcome in 63 (94%), and a mortality rate of 6%. Radiological intervention was carried out in 32 patients with a successful outcome for this modality alone in 23 (72%), with one death. Eight patients underwent surgery due to incomplete radiological control, with a successful outcome in 7 (88%), but with one death, giving an overall mortality of 6%. Throughout the 10-year period, there was a sequential decline in the use of primary surgical intervention in favour of a multi-modal radiology-surgery approach. Conclusion: Severe gastro-intestinal haemorrhage in the acute setting, when not amenable to successful endoscopic therapy remains a serious condition with significant mortality (6%). The introduction of interventional radiological techniques however now means that the majority of patients can be successfully managed without operative surgery, but this still plays an important role for complex or refractory patients. Competing interests: None declared.